tìm x biết:36:[7.(x-3)+4]=24:23
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a)x=\dfrac{1}{4}+\dfrac{5}{13}=\dfrac{33}{52}.\\ b)\dfrac{x}{3}=\dfrac{2}{3}+\dfrac{-1}{7}.\\ \Leftrightarrow\dfrac{x}{3}=\dfrac{11}{21}.\\ \Leftrightarrow\dfrac{7x}{21}=\dfrac{11}{21}.\\ \Rightarrow7x=11.\\ \Leftrightarrow x=\dfrac{11}{7}.\\ c)\dfrac{x}{3}=\dfrac{16}{24}+\dfrac{24}{36}=\dfrac{2}{3}+\dfrac{2}{3}=\dfrac{4}{3}.\\ \Rightarrow x=4.\\ d)\dfrac{x}{15}=\dfrac{1}{5}+\dfrac{2}{3}=\dfrac{13}{15}.\\ \Rightarrow x=13.\)
a) ( x - 266 ): 5 = 7
( x - 266 ) = 7 x 5
( x - 266 ) = 35
x = 35 + 266
x = 301
b) ( x - 129 ) x 4 = 36
( x - 129 ) = 36 : 4
( x - 129 ) = 9
x = 9 + 129
x = 138
c) 786 - x = 5 x 4 : 2
786 - x = 20 : 2
786 - x = 10
x = 786 - 10
x = 776
d) x + 24 : 4 x 3 = 285
x + 6 x 3 = 285
x + 18 = 285
x = 285 - 18
x = 267
a)73+86+968+914+3032
= (86 + 914) +(968 + 3032) + 73
= 1000 + 4000 + 73
= 5073
b)341.67+341.16+659.83
=341 (67 + 16) + 659 * 83
= 341 * 83 + 659 * 83
= (341+ 659) * 83
= 1000 * 83
= 830000
c)252-84:21+7
= 252 - 2 +7
=257
d)4.8.25.125.27
= (8 * 125) (4* 25) * 27
= 1000 * 100 * 27
= 2700000
e)34+35+36+37-24-25-26-27
= (34-24) + (35-25) + (36-26) + (37-27)
= 10 + 10 + 10 + 10
= 40
g)1-2+3-4+...-98+99
= (1 + 99) + (-2-98) + .....+ (-48 - 52) + (49 + 51) - 50
= 100 - 50
= 50
h)1-4+7-10+...-100+103
Bài 2:Tìm số nguyên x,biết:
l)3636:(12.x-91)=36
3636 : (12x - 91) = 36
12x - 91 = 101
12x = 192
x= 16
m)(x:23+45).67=8911
x: 23 + 45 = 133
x : 23 = 88
x= 88/23
n)[(6.x-39):7].4=12
6x - 39 = 3
6x = 42
x=7
p)128-3(x+4)=23
3(x+4) = 105
x+4= 35
x= 31
q)[(4.x+28).3+55]:5=35
(4x + 28)*3 +55 = 175
(4x + 28) * 3 = 120
4x + 28 = 40
4x = 12
x=3
r)123-5.(x+4)=38
5(x+4) = 85
x+4 = 17
x= 13
t)11-(53+x)=97
53 + x = -86
x= -139
i)23.75+25.23+180
= 23(75+25) + 180
= 2300 + 180
= 2480
a) \(58+7x=100\)
\(=>7x=100-58\)
\(=>7x=42\)
\(=>x=42:7\)
\(=>x=6\)
b) \(3x-7=28\)
\(=>3x=28+7\)
\(=>3x=35\)
\(=>x=35:3\)
\(=>x=\dfrac{35}{3}\)
c) \(x-56:4=16\)
\(=>x-14=16\)
\(=>x=16+14\)
\(=>x=30\)
d) \(101+\left(36-4x\right)=105\)
\(=>36-4x=105-101\)
\(=>36-4x=4\)
\(=>4x=36-4\)
\(=>4x=32\)
\(=>x=32:4\)
\(=>x=8\)
e) \(\left(x-12\right):12=12\)
\(=>x-12=12.12\)
\(=>x-12=144\)
\(=>x=144-12\)
\(=>x=132\)
f) \(\left(3x-2^4\right).7^3=2.7^4\)
\(=>3x-2^4=2.7^4:7^3\)
\(=>3x-16=2.7=14\)
\(=>3x=14+16\)
\(=>3x=30\)
\(=>x=30:3\)
\(=>x=10\)
i) \(\left(10+2x\right).4^{2011}=4^{2013}\)
\(=>10+2x=4^{2013}:4^{2011}\)
\(=>10+2x=4^2=16\)
\(=>2x=16-10\)
\(=>2x=6\)
\(=>x=6:2\)
\(=>x=3\)
\(#WendyDang\)
Bài 1:
a) \(\frac{16}{15}.\frac{\left(-5\right)}{14}.\frac{54}{24}.\frac{56}{21}\)
\(=\frac{4.2.2}{5.3}.\frac{\left(-5\right)}{2.7}.\frac{3.3}{4}.\frac{8}{3}\)
\(=\frac{4.2.2.\left(-5\right).3.3.8}{5.3.2.7.4.3}\)
\(=\frac{-16}{7}\)
b) \(\frac{7}{3}.\frac{\left(-5\right)}{2}.\frac{15}{21}.\frac{4}{\left(-5\right)}\)
\(=\frac{7}{3}.\frac{\left(-5\right)}{2}.\frac{5}{7}.\frac{2.2}{\left(-5\right)}\)
\(=\frac{7.\left(-5\right).5.2.2}{3.2.7.\left(-5\right)}\)
\(=\frac{10}{3}\)
Bài 2:
a) \(\frac{21}{24}.\frac{11}{9}.\frac{5}{7}=\frac{7}{8}.\frac{11}{9}.\frac{5}{7}=\frac{11.5}{8.9}=\frac{55}{72}\)
b) \(\frac{5}{23}.\frac{17}{26}+\frac{5}{23}.\frac{9}{26}\)
\(=\frac{5}{23}.\left(\frac{17}{26}+\frac{9}{26}\right)=\frac{5}{23}.1=\frac{5}{23}\)
c) \(\left(\frac{3}{29}-\frac{1}{5}\right).\frac{29}{3}=\frac{3}{29}.\frac{29}{3}-\frac{1}{5}.\frac{29}{3}\)
\(=1-1\frac{14}{15}=\frac{14}{15}\)
Bài 3:
a) x/5 = 2/5
=> x =2
b) -4/x = 20/14 = 10/7
=> -4/x = 10/7
=> x.10 = (-4).7
x.10 = - 28
x= -28 :10
x= -2,8
c) 4/7 = 12/x = 12/ 21
=> 12/x = 12/21
=> x = 21
d) 3/7 = x / 21 = 9/21
=> x/21 = 9/21
=> x= 9
36:[7.(x-3)+4]=2
7.(x-3)+4=36:2
7.(x-3)=18-4
x-3=14:7
x=2+3
x=5